2008
DOI: 10.1111/j.1462-2920.2007.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of a thermophilic ammonia oxidizing archaeon synthesizing crenarchaeol

Abstract: The widespread occurrence and diversity of ammonia oxidizing Archaea suggests their contribution to the nitrogen cycle is of global significance. Their distribution appeared limited to low- and moderate-temperature environments until the recent finding of a diagnostic membrane lipid, crenarchaeol, in terrestrial hot springs. We report here the cultivation of a thermophilic nitrifier ('Candidatus Nitrosocaldus yellowstonii'), an autotrophic crenarchaeote growing up to 74 degrees C by aerobic ammonia oxidation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
515
3
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(546 citation statements)
references
References 44 publications
22
515
3
6
Order By: Relevance
“…The information about the effect of heavy metal on AOA was still limited up to now. Although it was reported that AOA might be in general less susceptible than AOB to inhibitor because of the remarkably different physiological characteristics of archaea compared with bacteria (Schauss et al 2009), the mechanistic information about the response of AOA to environmental stress remains to be unclear due to limited cultivated AOA cluster so far (Konneke et al 2005;de la Torre et al 2008). According to the results in this study, it was not an appropriate option to use the amoA gene copy number of AOB or AOA for the purpose of soil pollution assessment.…”
Section: Discussionmentioning
confidence: 74%
“…The information about the effect of heavy metal on AOA was still limited up to now. Although it was reported that AOA might be in general less susceptible than AOB to inhibitor because of the remarkably different physiological characteristics of archaea compared with bacteria (Schauss et al 2009), the mechanistic information about the response of AOA to environmental stress remains to be unclear due to limited cultivated AOA cluster so far (Konneke et al 2005;de la Torre et al 2008). According to the results in this study, it was not an appropriate option to use the amoA gene copy number of AOB or AOA for the purpose of soil pollution assessment.…”
Section: Discussionmentioning
confidence: 74%
“…The recent discovery of 'Candidatus Nitrosocaldus yellowstonii', an archaeon that grows up to 74°C, however broadened the phylogenetic spectrum of ammonia oxidizers active at high temperatures (de la Torre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…in situ production of a small amount of IPL iGDGTs in the oxidized sediment by sedimentary aerobic Thaumarchaeota. These likely function via aerobic oxidation of ammonium (Könneke et al, 2005;Wuchter et al, 2006b;de la Torre et al, 2008;Walker et al, 2010;Tourna et al, 2011), formed from the break-down of OM when O 2 was penetrating into the sediments. To examine the oxic degradation and potential production of individual IPL iGDGTs, we performed direct analysis of IPL crenarchaeol.…”
Section: Oxic Degradation Of Igdgts CL and Iplmentioning
confidence: 99%